The Influence Of Product, Price, Location And Store Atmosphere On Customer Satisfaction At Warkop Markas Cofee - Hamzah Siregar; Zulkarnaen Nasution; Bayu Eko Broto (STIE AMKOP, 2023)
This study aims to analyze and determine the effect of Product, Price, Location and Store Atmosphere on Customer Satisfaction at Warkop Markas Cofee. The population used in this study were 96 respondents who visited and made repeated purchases more than 3 times at Warkop Markas Cofee. The data collection technique in this study used the one shot method or one-time measurement of 96 respondents. While the data analysis technique used is multiple linear regression analysis and uses the SPSS application. Partially, the product has a positive and significant impact on customer satisfaction at Warkop Markas Cofee. Partially Price has a positive and significant influence on customer satisfaction at Warkop Markas Cofee . Partially, location has a positive and significant influence on customer satisfaction at Warkop Markas Cofe. Partially Store Atmosphere has a positive and significant influence on customer satisfaction at Warkop Markas Coffee. Simultaneously the product, price, location, and store atmosphere variables together or simultaneously have a positive and significant effect on customer satisfaction at Warkop Markas Cofee. Kata Kunci: Product, Price, Location, Store Atmesphere, Customer Satisfaction